The investigation of contact performance of oxide reinforced copper composite via mechanical alloying - Guler, Omer; Evin, Ertan (Elsevier Science Sa, 2009)
In this study, the electrical performance of ODS Cu-based contact materials produced by mechanical alloying (MA) was investigated. Cu-based powder mixtures that contain various oxides at different proportions were milled by the high energy planetary ball mill for 5 h. Mechanically alloyed powder mixtures containing ZnO, Al2O3 and Y2O3 at the ratios of 1, 2, 4 and 6 wt.% were pressed and sintered at 800 degrees C in vacuum environment. These compacts were then forged axially at the ratio of 75% at 650 degrees C so as to increase the density. At the first step, electrical conductivity experiments were applied to these samples to determine the best conductivity Results showed that, reinforced Cu samples containing 4% oxides exhibited the best. At the second step, contact count experiments were made with these samples for determining contact performance for the counts of 3000, 6000 and 9000 turn on/off. The samples of 4 wt.% ZnO, 4 wt.% Al2O3, 4 wt.% Y2O3 reinforced Cu materials, respectively, exhibited both the best conductivity and the best contact performances. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Mechanical alloying; High energy ball milling; ODS copper; Electrical properties